Epigastric Fullness - Georg Stacher (Canadian Journal of Gastroenterology)
Epigastric fullness may be caused by a disordered gastric motor function, resulting in delayed gastric emptying, but may also be caused by rapid emptying, leading to a distention of the proximal small intestine. A rational diagnostic approach to a patient complaining of epigastric fullness is needed to reveal the underlying disorder or disease and to enable an adequate, targeted therapy. The clinical impression based on symptoms is unreliable and cannot distinguish function disorders and benign disease from severe conditions.